2021
DOI: 10.1097/mpa.0000000000001932
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2 Chinese Primary Pancreatic Ductal Adenocarcinoma Cancer Cell Lines and Their Phenotypes

Abstract: Objectives: Pancreatic cancer (PC) is one of the most lethal cancers. Currently, the most commonly used PC cell lines were all derived from White individuals, and few models can be used to study in Asian populations. In China, the incidence of PC is increasing every year, highlighting the need to develop new Chinese PC cell lines for cancer research.Methods: A total of 203 patients diagnosed with PC, enrolled from January 2012 to December 2017 in our hospital (Department of Hepatobiliary and Pancreatic Surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A recent study found that Ro60 levels are highly expressed in the nuclei of pancreatic cancer cells. 1 It was found that downregulation of Ro60 inhibited tumorigenesis in vivo, as well as proliferation, migration, and invasion of pancreatic ductal adenocarcinoma. 1 We describe a patient with pancreaticobiliary ampullary adenocarcinoma who 1 year before diagnosis was evaluated for autoimmune disease.…”
Section: Anti-ro60 Antibodies Utility As a Diagnostic Indicator Of Pa...mentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study found that Ro60 levels are highly expressed in the nuclei of pancreatic cancer cells. 1 It was found that downregulation of Ro60 inhibited tumorigenesis in vivo, as well as proliferation, migration, and invasion of pancreatic ductal adenocarcinoma. 1 We describe a patient with pancreaticobiliary ampullary adenocarcinoma who 1 year before diagnosis was evaluated for autoimmune disease.…”
Section: Anti-ro60 Antibodies Utility As a Diagnostic Indicator Of Pa...mentioning
confidence: 99%
“…1 It was found that downregulation of Ro60 inhibited tumorigenesis in vivo, as well as proliferation, migration, and invasion of pancreatic ductal adenocarcinoma. 1 We describe a patient with pancreaticobiliary ampullary adenocarcinoma who 1 year before diagnosis was evaluated for autoimmune disease. Despite every other marker of autoimmunity being negative, the anti-Ro60 marker was extremely elevated at 564.9 chemiluminescent units.…”
Section: Anti-ro60 Antibodies Utility As a Diagnostic Indicator Of Pa...mentioning
confidence: 99%
See 3 more Smart Citations